2013
DOI: 10.2147/ijn.s50837
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and antimicrobial properties of copper nanoparticles

Abstract: Copper nanoparticle synthesis has been gaining attention due to its availability. However, factors such as agglomeration and rapid oxidation have made it a difficult research area. In the present work, pure copper nanoparticles were prepared in the presence of a chitosan stabilizer through chemical means. The purity of the nanoparticles was authenticated using different characterization techniques, including ultraviolet visible spectroscopy, transmission electron microscopy, X-ray diffraction, Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(81 citation statements)
references
References 46 publications
4
68
0
2
Order By: Relevance
“…This has been attributed to the greater abundance of amines and carboxyl groups on the cell surface of B. subtilis for which Cu has a high affinity. Cu ions may also interact with DNA molecules, intercalate with nucleic acid strands, and/or disrupt biochemical processes [83,84]. Titanium dioxide ( TiO 2 ) nanoparticles have also been explored to fight infection.…”
Section: Topical Applications Of Nanoparticlesmentioning
confidence: 99%
“…This has been attributed to the greater abundance of amines and carboxyl groups on the cell surface of B. subtilis for which Cu has a high affinity. Cu ions may also interact with DNA molecules, intercalate with nucleic acid strands, and/or disrupt biochemical processes [83,84]. Titanium dioxide ( TiO 2 ) nanoparticles have also been explored to fight infection.…”
Section: Topical Applications Of Nanoparticlesmentioning
confidence: 99%
“…Among the different reported approaches, the widely accepted solution-based chemical precipitation method generally involves the precipitation of Cu-NPs or Cu-nanocomposites through reduction of copper salts at optimal precursor concentrations under inert atmosphere (Ar or N 2 ). Here the particle size of Cu-NPs is manipulated by controlling the process parameters, whereas their stability is often achieved through the use of various stabilizing agents (added in appropriate solvent medium), such as starch (Valodkar et al 2012), gelatin (Chatterjee et al 2012), chitosan (Usman et al 2013), sodium dodecyl sulfate (Soomro et al 2013), cetyltrimethylammonium bromide (Wu and Chen 2004), and so on (Mott et al 2007;Song et al 2004;Zhang et al 2014;Pulkkinen et al 2009;Wang and Asefa 2010;Giuffrida et al 2008;Sarkar et al 2008;Deng et al 2013). Their presence in solvent medium during the preparation not only helps in preventing surface oxidation of the Cu-NPs to form Cu 2 O and CuO but also helps in controlling their particle size to obtain stable, colloidal dispersions.…”
Section: Introductionmentioning
confidence: 99%
“…Here, CMC is used as a stabilizing agent that assists in obtaining stable, aqueous colloidal dispersion of Cu-NPs. Facile synthesis of CMC-stabilized Cu-NPs (CMC-Cu-NPs) produces particles of high-quality, while most of the existing methods (Chatterjee et al 2012;Usman et al 2013) of Cu-NPs synthesis produce particles having limited stability and/or poor aqueous dispersibility in time-consuming way (For comparison with other methods, see Section 1 under 'Supplementary Material 1').…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that nanoparticulate formulations might be used as effective bactericidal materials (14). It was reported that metal nanoparticles (Ag, Cu, CuO, Au) exhibited a wide spectrum of antimicrobial activities against different microorganisms, including fungi and Gram-positive and Gram-negative bacteria (15).…”
mentioning
confidence: 99%
“…Several techniques, such as thermal reduction, the capping agent method, sonochemical reduction, metal vapor synthesis, the microemulsion technique, laser irradiation, and induced radiation, can be used to prepare copper nanoparticles (15). Most of these techniques require organic solvents and a high temperature and involve multistep sample preparation processes (19).…”
mentioning
confidence: 99%